MENGUAK BEBERAPA DIMENSI BUDAYA KERAJAAN ACEH (Sebuah Kajian Historis) - Amirul Hadi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2008)
Abstract: Exploring Some Cultural Dimensions of Acehnese Sultanates: An Historical Study. Culture constitutes a significant dimension of the life of community. As a concept, experts in general define culture as an ideational system, which include ideas, concepts, rules, and meanings that are shared by community and expressed in daily life. In its history, especially during the 17th century, Aceh, as an Islamic kingdom, developed its own culture, as it was evident in the state’s institutions and behaviors. This includes, among others, political, intellectual, ceremonial, and cosmopolitan and tolerant culture. All these were induced by the Islamic character of the kingdom, which was also enriched by its Acehnese and Southeast Asian elements.Kata Kunci: budaya, kerajaan, Aceh, dan Islam